Psychosocial and nutritional factors of cognitive disorders in Central Africa - (:unkn) unknown (My University, 2014)
With the aging of the world population, prevalence of non-communicable diseases including dementia is increasing. While epidemiological studies on cognitive impairments have been mainly conducted in high-income countries, a few have been carried out in low-and middle-income countries, including African countries, not exempt from this phenomenon. The EPIDEMCA program, Epidemiology of Dementia in Central Africa, is aimed at contributing to a better understanding of dementia and Alzheimer's disease in rural and urban areas in two countries of Central Africa: the Central African Republic (CAR) and the Republic of Congo (ROC). This PhD thesis, which is part of this program, focuses on the relationship between cognitive disorders (Mild Cognitive Impairment (MCI) and dementia) and psychosocial factors (stressful life events and dependent personality disorder) on the one hand, and nutritional factors (undernutrition and dietary consumption) on the other.The EPIDEMCA program is a cross-sectional multicenter population-based epidemiological study carried out among people aged 65 years and over in rural and urban areas of CAR and ROC between 2011 and 2012 using a two-phase design. DSM-IV and Petersen criteria were required for a diagnosis of dementia and MCI, respectively. Among 2002 subjects who agreed to participate in the study, cognitive status and reliable age were available for 1772 people: 1519 were free of cognitive impairment, 118 suffered from had MCI and 135 from had dementia. As regards the psychosocial factors, our first study showed that MCI was positively associated with the total number of events experienced throughout a life span in Congo only, and, with the total number of events from the age of 65 onwards and with a child’s severe physical disease after the age of 65 in the total sample. On the contrary, dementia was associated with neither the accumulation of stressful life events nor individual events. Results of our second study showed tha
Keywords: African Research